Caffeine ingestion after rapid weight loss in judo athletes reduces perceived effort and increases plasma lactate concentration without improving performance - Lopes-Silva, J. P.; Felippe, L. J. C.; Silva-Cavalcante, M. D.; Bertuzzi, R.; Lima-Silva, A. E. (Nutrients, 2014)
The objective of this study was to examine the effect of caffeine on judo performance, perceived exertion, and plasma lactate response when ingested during recovery from a 5-day weight loss period. Six judokas performed two cycles of a 5-day rapid weight loss procedure to reduce their body weight by ~5%. After weigh-in, subjects re-fed and rehydrated over a 4-h recovery period. In the third hour of this "loading period", subjects ingested a capsule containing either caffeine (6 mg·kg-1) or placebo. One hour later, participants performed three bouts of a judo fitness test with 5-min recovery periods. Perceived exertion and plasma lactate were measured before and immediately after each test bout. Body weight was reduced in both caffeine and placebo conditions after the weight loss period (-3.9% ± 1.6% and -4.0% ± 2.3% from control, respectively, p < 0.05). At three hours after weigh-in, body weight had increased with both treatments but remained below the control (-3.0% ± 1.3% and -2.7% ± 2.2%). There were no significant differences in the number of throws between the control, caffeine or placebo groups. However, plasma lactate was systemically higher and perceived exertion lower in the subjects who ingested caffeine compared to either the control or placebo subjects (p < 0.05). In conclusion, caffeine did not improve performance during the judo fitness test after a 5-day weight loss period, but reduced perceived exertion and increased plasma lactate.